Social and economic effects of rural tourism on the development of rural areas - Oleg Petelca; Veronica Garbuz (CES Working Papers, 2020)
The article focused on determining the effects of rural tourism on the social and economic situation of rural areas. The research was carried out on the basis of data collected from the National Bureau of Statistics of the Republic of Moldova for the period 2015-2020. There were analysed indicators reflecting the evolution of rural tourism such as attendance of establishments, capacity of establishments, number of tourists placed in establishments of collective touristic reception with functions of accommodation, number of overnight stays in establishments of collective touristic reception with functions of accommodation and indicators that reflect the socio-economical situation of rural areas in the Republic of Moldova such as households equipment by dwelling facilities, disposable incomes of population, employed population. The results showed the relatively small positive trend of indicators reflecting the evolution of tourism in rural areas of the Republic of Moldova and a weak, but positive effect on households equipment by dwelling facilities and disposable incomes of population.
Keywords: 330; rural tourism; agricultural tourism; development; rural area; recreation